KNOWLEDGE POWER MODEL ACCORDING TO MICHEL FOUCAULT ON NEWS TEXT THEMED CHANGES IN FUEL PRICES - ruhiman ruhiman; Rida Khamilawati; Rochmat Tri Sudrajat (JLER (Journal of Language Education Research), 2019)
The thought arises and develops based on the socio-cultural state of every human being, which then forms the distinctiveness of thought. Without realizing the thought of each individual has been monopolized by the ruler in a different sense. The ruler, in this case, as stated by Michel Foucault, that rationality and subjectivity of thought does not seem given and natural but are dominated by dominators who exploit some other people as a result of discourse. Gradually the influence of power has an impact on the ways of thinking and acting of dominant groups. One way that the ruling group built to strengthen the concept of "truth" through discourse. This article shows how power tries to make new concepts of truth in certain situations. The method used in this research is descriptive-qualitative analyzing the news text entitled, "Minister Jonan: BBM Premium Does Not Rise, Pertamax Adjust Prices" on news on lineTempo.co edition Thursday, September 6, 2018. Data collection is done through, (1) read and understand the news text being researched in order to obtain a clear understanding of the contents of the news, (2) mark parts of the news relating to Foucault's theory of power-knowledge, and (3) inventory the sentences in the news relating to Foucault's power-knowledge theory. This research shows that the new term that was rolled out by the authorities through news discourse aims to erase the public's perception of the truth they have always believed.